Effect of different volume fraction of steel fiber/graphite on thermal conductivity and compressive properties of concrete - Ren, Xiang; Ding, Yunxiang; Liu, Qunfeng; Chen, Shaojie; Song, Fei (Frontiers in Materials, 2022)
The enhancement of the thermal conductivity can be utilized to reduce the temperature difference between the internal and external structural surfaces and thus the thermal induced stresses in concrete. In this study, the compressive strength and thermal conductivity were investigated in concrete structures enhanced by the steel fiber and graphite at different volume fractions. First, the cubic and the cylinder concrete samples were fabricated by adding different volume fractions of the steel fibers, such as 0%, 0.5%, 1.0%, 1.5%, 2.0%, and 2.5%, to the concrete mixture. The fiber enhanced samples were tested following the standard procedures, and the optimal compressive strength and thermal conductivity can be obtained in the sample with the volume fraction of steel fiber at 1.5%. Moreover, graphite powders with different volume proportions at 5%, 10%, and 15% were added to the fiber enhanced concrete samples with the identical size. The compressive strength and thermal conductivity tests were also performed and the optimal content of steel fiber was 1.5%, and the graphite was 5%. This could not only meet the design requirements the compressive strength of the concrete, but also improve the thermal conductivity of the concrete. The research results could provide some reference for the design of the high thermal conductivity concrete.